1994
DOI: 10.1007/bf00010732
|View full text |Cite
|
Sign up to set email alerts
|

Molluscan cellulolytic activity responses to zinc exposure in laboratory and field stream comparisons

Abstract: Changes in cellulolytic activity of Asiatic clams (Corbiculafluminea) and snails (Mudalia dilatata) were monitored throughout 30-d exposures to constant additions (0.0, 0.025, 0.05, 0.50, and 1.0 mg l-') of zinc (Zn). All exposures of 0.05 mg Zn l-' or greater significantly reduced enzyme activity (exo-and endocellulase) in both molluscs as early as 10 d following exposures in outdoor laboratory streams incorporating New River water as diluent. More sterile laboratory stream exposures were less consistent in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0
2

Year Published

1997
1997
2012
2012

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 37 publications
0
14
0
2
Order By: Relevance
“…Conducted well, these systems will provide ecologically realistic, relevant, and interpretable findings for use in ecological risk assessment and the use of low application factors to project responses in the real world. Farris et al, 1989Farris et al, , 1994Genter et al, 1987, , 1993aSchwab et al, 1992;Cuffney et al, 1990 12 Landrum et al, 1984;Giesy et al, 1983aGiesy et al, , 1983b Pignatello et al, 1986;Hedtke and Arthur, 1985;Hedtke et al, 1986 540.00 Hedtke et al, 1989;Pratt and Bowers, 1990;Schultz and Hermanutz, 1990;Hermanutz, 1990 540 …”
Section: Discussionmentioning
confidence: 95%
“…Conducted well, these systems will provide ecologically realistic, relevant, and interpretable findings for use in ecological risk assessment and the use of low application factors to project responses in the real world. Farris et al, 1989Farris et al, , 1994Genter et al, 1987, , 1993aSchwab et al, 1992;Cuffney et al, 1990 12 Landrum et al, 1984;Giesy et al, 1983aGiesy et al, , 1983b Pignatello et al, 1986;Hedtke and Arthur, 1985;Hedtke et al, 1986 540.00 Hedtke et al, 1989;Pratt and Bowers, 1990;Schultz and Hermanutz, 1990;Hermanutz, 1990 540 …”
Section: Discussionmentioning
confidence: 95%
“…Several authors have reported a depression of digestive carbohydrase activities in invertebrate species exposed in vitro or in situ to chemical pollutants, especially heavy metals (Farris et al 1994;Yan et al 1996;De Coen and Janssen 1997;Milam and Farris 1998;Barfield et al 2001;Chen et al 2002;Le Bihan et al 2004;Li et al 2008;Dedourge-Geffard et al 2009;Kalman et al 2009;Boldina-Cosqueric et al 2010;Bourgeault et al 2010). Digestive enzyme response to chemical stressors may actually be rather complex (Fig.…”
Section: Digestive Enzyme Responses: Integration Of Natural and Man-mmentioning
confidence: 95%
“…Digestive enzyme response to chemical stressors may actually be rather complex (Fig. 8) and depends, among others, on exposure time, toxicant concentration and exposure route (Farris et al 1994;De Coen and Janssen 1997). Toxic contaminants present in water may initially lead to a reduction of mussel energy inputs as a result of decreased food availability (reduced phytoplankton productivity) (Jantz and Neumann 1998) and/or decreased food intake (reduced filtration activity, increased valve-closure duration) (Borcherding 1992;Kraak et al 1993).…”
Section: Digestive Enzyme Responses: Integration Of Natural and Man-mmentioning
confidence: 98%
“…If chronic exposures are defined by one tenth of the organism's life span, then a chronic test for Leptoxis praerosa (voucher specimens identified by Dr. R. Dillon, University of South Carolina, USA), a semelparous, biennial pleurocerid snail, should last approximately 70 d, assuming a 2‐year life span [11,12]. Exposures of 10 d to 50 μg Zn/L or greater [13] and exposures of 20 d to power plant effluents [14] have been shown to impair cellulolytic enzyme activity in Mudalia dilatata , a species closely related to Leptoxis spp. Although Zn exposures of up to 60 d have been conducted with snails [14], long‐term implications of reduced cellulolytic enzyme activity were not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, changes in enzyme activity may be the result of a combination of these or other toxicity mechanisms. Because the exact mechanism of toxicity and cause of metal‐induced enzyme activity impairment were not fully understood in earlier studies [13], actual chronic effects were difficult to predict without conducting long‐term chronic studies. The objective of this study was to determine whether metal impairments are cumulative and/or whether acclimation occurs by examining long‐term effects from exposure to Cu and Zn CSC concentrations on the snail L. praerosa .…”
Section: Introductionmentioning
confidence: 99%